2015
DOI: 10.1080/17461391.2015.1061058
|View full text |Cite
|
Sign up to set email alerts
|

Exercise training modifies walking kinematics and energy cost in obese adolescents: A pilot controlled trial

Abstract: The aim of this study was to investigate the effects of a weight loss intervention based on physical exercise on the relationship between energy cost and stride frequency during walking in obese teenagers. Participants aged 13-16 years old were assigned to a training (n = 14) and control (n = 10) groups. During eight weeks, the training group performed three 60-min weekly sessions of high-intensity intermittent activities coupled with aerobic training. Body composition, gait parameters and energy cost during 4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
10
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(11 citation statements)
references
References 51 publications
1
10
0
Order By: Relevance
“…The exercise component was specifically focused on improving locomotion, and included exercises such as skipping rope and jumping on different surfaces. In a different study, Delextrat et al [ 56 ] found improved biomechanics after adolescents participated in a weight loss intervention which included three 60-min sessions per week, for a period of eight weeks. In addition to other benefits, the authors found that participants’ walking speed increased by 23% and the energy cost of walking at different frequencies was decreased.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The exercise component was specifically focused on improving locomotion, and included exercises such as skipping rope and jumping on different surfaces. In a different study, Delextrat et al [ 56 ] found improved biomechanics after adolescents participated in a weight loss intervention which included three 60-min sessions per week, for a period of eight weeks. In addition to other benefits, the authors found that participants’ walking speed increased by 23% and the energy cost of walking at different frequencies was decreased.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast to the overall improvements observed however, we did find a reduction in velocity from pre- to post-yoga, and increases in walking speed are almost always viewed as an improvement. For example, Delextrat et al [ 56 ] found a large and significant increase in gait velocity after their weight loss intervention for youth with obesity. However, increased velocity actually increases the force on the knee [ 59 ], which could potentially put these youth at greater risk of injury.…”
Section: Discussionmentioning
confidence: 99%
“…We only identified three previous studies testing the effects of exercise on gait biomechanics in children and adolescents with OW/OB 8–10 . Unlike Delextrat et al, 10 we could not test changes in walking speed since we maintained the speed that children had self‐selected pre‐exercise 19,28 .…”
Section: Discussionmentioning
confidence: 99%
“…An 8‐week high‐intensity aerobic program had positive effects on gait speed and energetic efficiency in adolescents aged 13–16 years old with obesity 10 8,9 .…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation